Lasing: Host Exciton Confinement for Enhanced Förster‐Transfer‐Blend Gain Media Yielding Highly Efficient Yellow‐Green Lasers (Adv. Funct. Mater. 17/2018). (23rd April 2018) - Zhang, Qi; Liu, Jingguan; Wei, Qi; Guo, Xiangru; Xu, Yan; Xia, Ruidong; Xie, Linghai; Qian, Yan; Sun, Chen; Lüer, Larry; Cabanillas‐Gonzalez, Juan; Bradley, Donal D. C.; et al.
Abstract : Selecting suitable hosts for green laser emission guest polymers like F8BT remains challenging, with efficient Förster resonance energy transfer and high photoluminescence quantum efficiency being necessary, but not sufficient criteria. In article number 1705824, Ruidong Xia, Yan Qian, Donal D. C. Bradley, Wei Huang, and co‐workers demonstrate that hosts with short‐time, charged‐state absorption (upper panels) quench gain whereas hosts that delay charge generation (lower panels) allow lasing.